2019
DOI: 10.1002/cctc.201901127
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Doped Ternary and Quaternary Transition‐Metal‐Based Electrocatalysts for Hydrogen Evolution Reaction

Abstract: Electrocatalytic hydrogen evolution reaction (HER) through transition‐metal‐based (TMB) catalysts represents a totally sustainable and cost‐effective technology for practical hydrogen (H2) production with high purity. Unfortunately, most of the catalysts have the unsuitable hydrogen adsorption behavior and thereby insufficient H2 generation efficiency. The general strategy to address the problem is to introduce various cation or/and anion dopants for designing multivariate TMB catalysts, which comes down to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 167 publications
0
10
0
Order By: Relevance
“…6,7 Moreover, various metal-and heteroatom-doped carbon nanomaterial composite catalysts have emerged as promising alternatives as well. 8,9 In addition to promoting fast charge transfer kinetically, another simple strategy is to expand the catalytic surface area by fabricating porous electrodes, templating with carbon substrates, and decreasing the size of active materials to the nanoscale level. 9,10 High surface area is critical to provide high current density and capacitance by increasing the number of active sites for electrochemical surface reactions and facilitating the mass transfer of reactants inside the active layer on the electrode (Figure 1).…”
Section: ■ Key Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Moreover, various metal-and heteroatom-doped carbon nanomaterial composite catalysts have emerged as promising alternatives as well. 8,9 In addition to promoting fast charge transfer kinetically, another simple strategy is to expand the catalytic surface area by fabricating porous electrodes, templating with carbon substrates, and decreasing the size of active materials to the nanoscale level. 9,10 High surface area is critical to provide high current density and capacitance by increasing the number of active sites for electrochemical surface reactions and facilitating the mass transfer of reactants inside the active layer on the electrode (Figure 1).…”
Section: ■ Key Referencesmentioning
confidence: 99%
“…Although Pt and Pt-based materials were long considered to be the best electrocatalysts because of their high performance and efficiency, many researchers have worked to develop alternative electrocatalysts because of the limited supply and high cost of Pt. For example, nanostructured bimetallic electrocatalysts employing an alloy and core–shell structure have been proposed to overcome sluggish catalytic reactions. , Moreover, various metal- and heteroatom-doped carbon nanomaterial composite catalysts have emerged as promising alternatives as well. , …”
Section: Introductionmentioning
confidence: 99%
“…19) is lower than those of C (2.55) and N (3.04), suggesting that P-doping may be an efficient method to optimize the electronic structure of Mo 2 C for improving HER kinetics. 46 Inspired by the aforementioned discussions, in this work, we report a scalable and facile strategy to develop a highly active and stable electrocatalyst of P and Ni codoped Mo 2 C encapsulated in N-doped carbon (P/Ni−Mo 2 C@NC) for the HER. P/Ni−Mo 2 C@NC-800 shows the best electrocatalytic activity with a low overpotential of 165 mV at 10 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar observation has been shown that Mo 2 C doped with Ni also exhibited an enhanced activity in the electrocatalytic HER. , Meanwhile, nitrogen-doped carbon matrix has been extensively demonstrated to promote the HER activity of Mo 2 C, because the carbon matrix endows the catalytic systems with improved electrical conductivity, and uniformly dispersed Mo 2 C nanoparticles with abundant exposed active sites. , Though metal cations were widely investigated as dopants to improve the HER catalytic performance of Mo 2 C, the metal-free anions were scarcely applied to optimize the electronic structure of Mo 2 C. The electronic-rich p-band of metal-free elements (e.g., S, P, N) can hybrid with the d-band of Mo 2 C, resulting in optimization of the electronic structure of Mo 2 C. For example, N-doped Mo 2 C has been investigated to provide more active sites for the HER . Besides this, the electronegativity of P (2.19) is lower than those of C (2.55) and N (3.04), suggesting that P-doping may be an efficient method to optimize the electronic structure of Mo 2 C for improving HER kinetics …”
Section: Introductionmentioning
confidence: 99%
“… 32 Moreover, considering the lower electronegativity of P (2.19) than that of C (2.55), N (3.04), and S (2.58), P-doping is believed to be a more attractive way to optimize the electronic configuration of Mo 2 C for accelerating HER kinetics. 33 Previous P-doping methods of adopting a P-containing salt ( e.g. sodium hypophosphite 34 ) or organic compounds ( e.g.…”
Section: Introductionmentioning
confidence: 99%